The Potency and Use of Tamarindus indica on Various Therapies - Candra Rini Hasanah Putri (Universitas Wijaya Kusuma Surabaya, 2014)
The use of natural materials for medical purposes is still being conducted by the public. One of the natural substances that are believed to play a role in health is Tamarindus indica. In Indonesia, the material is referred to as